Evaluasi dan Analisis Kolam Retensi Pengendalian Banjir: Studi Kasus Kolam Retensi Brimob Kota Palembang - Tri Fitriana; Taufik Ari Gunawan; Imroatul Chalimah Juliana (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2021)
Brimob retention basin is located within the Sekanak Sub-watershed system, which is a flood-prone point. Administratively, the Brimob retention basin area is a part of the Sub-district of Ilir Barat I. The research method used is computer modeling. The steps taken are data collection, hydrological analysis, cross-sectional analysis, hydrological and hydraulic modeling using pumps. The Brimob retention basin can accommodate a volume of water up to 115,103.73 m3, up to an elevation of the embankment of + 4.30 m. The magnitude of designed rainfall is R2 = 118.78 mm, R5 = 144.78 mm, R10 = 161.99 mm and R25 = 183.73 mm. The peak discharge of each return period is Q2 = 6.30 m3 / s, Q5 = 7.67 m3/s, Q10 = 8.59 m3/s and Q25 = 9.74 m3/s. To assess the effectiveness of pump operation, 2 (two) pumping capacities are simulated, namely: 250 l / sec and 500 l / sec, each used 2 (two) pump units. The simulation used a pump with a capacity of 500 l / sec, and the amount of discharge (inflow) for each return period is as input. The conclusion is that the use of a pump with a capacity of 500 l / sec can overcome excess water volume and avoid runoff and be effective in dealing with the excess water in the Brimob retention basin.